Proof of concept measurement of ovine intertrochanteric fracture stability with an X-ray visualized implantable screw bending sensor - Nathan T. Carrington; Savannah R. Forrester; Paul W. Milhouse; Caleb J. Behrend; Tom B. Pace; Kyle Jeray; Jeffrey N. Anker; John D. DesJardins (Scientific Reports)
Abstract Bone healing after internal fixation of intertrochanteric hip fractures is difficult to monitor with radiography, particularly with sliding hip screws (SHS). In this proof-of-concept study, we develop an ovine hip fracture model and use it to evaluate a novel sliding hip screw system with a sensor that can non-invasively detect bending of the screw implant during healing. An existing SHS implant was modified and implanted in a Suffolk Ewe sheep. A straight, radiodense 1 mm tungsten rod was attached to the screw in the cannula to enable quantification of screw bending by radiographically observing relative position of the rod compared to the screw tip. After surgery, weekly loaded and unloaded radiographs were taken of the femur. Once fracture stabilization had been indicated for at least three weeks, the femur was extracted and potted and radiographs were taken under simulated axial loading from 5 to 400 N. By week 3, full in vivo weight bearing over the fractured femur was achieved. In response, implant loading was clearly observed with the novel sensor. This observed implant loading continued until week 8, wherein it ceased entirely. Upon extraction, the femur showed a fully developed and very stable callus surrounding the fracture site. Subsequent mechanical tests confirmed no measurable implant loading under axial loads of up to 400 N. This test indicates that the proposed ovine model produces sufficient force over an SHS implant in an induced fracture. This allowed our sensor to indicate fracture healing through radiography in load scenarios greater than 25 kg.